Suitable Soil Conservation plants for Madras State - Madhavarao, S; Ramalingam, C.; Sundararaj, D. (Journal of Soil and Water Conservation, 2022)
Among the measures taken up by the Central aild State Governments in the soil conservation programme, the biological approach has been given its due importance. Researches on the suitable species of plants for being used in the soil conservation work have been initiated at different centres in the country. From a study of the rootsystem of a few grasses, Rao, Ramalingan and Ramaswamy (1964) have recommended Phalaris tuberosa and Dactylis glotherata to be best suited’ for protection of bench terraces on the hills and LCenchrus ciliari s and C. glaucus for the contour builds of the plains. Rama Rao (1962), Srinivasan, Bonde and Tejwani (1962), Agarwal and Rege (1960) and Bhimayya, Bonde and Srinivasan (1956) have brought out importance of vegetational cover in soil consei-vation and dealt on species found suitable by them.